Social, economic and environmental determinants of active aging in the elderly attended in a center of integral health care - Sanni Moraes de Oliveira; Keylla Talitha Fernandes Barbosa; Fabiana Maria Rodrigues Lopes de Oliveira; Wiliana Aparecida Alves de Brito Fernandes; Maria das Graças Melo Fernandes (Universidad de Alicante, 2018)
The aim of this study is to evaluate social, economic, and environmental determinants of active aging in older adults assisted at the Center for Integrated Health Care to elderly in João Pessoa, Paraiba. It is a descriptive, transversal study, with a qualitative approach. The target population consisted all older adults (n=224) assisted at the Center for Integrated Health Care. Data collection was conducted through semi-structured interview guide in the period from October to December of 2014. The majority of older adults were among the age group of 60 to 69 years old, and the most of them were female. A number of years of study were between 4 to 8. The vast majority of this population does not have a paid work, and they receive a monthly income between 1 to 3 minimum wage. The most predominant source of social benefit was retiring. The theft was the type of violence the most experienced. The most of them live in their own house with a good physical structure and basic sanitation, but these homes have risks to cause accidental fall. This study is important for reflection and attitude towards of health professionals to improve care for the elder population. Therefore, the care for elderly can understand their necessities and promote autonomy emphasizing social, economic, and environmental determinants of active aging.